Celiac Disease and Non-Celiac Gluten Sensitivity - Rodrigo, Luis (IntechOpen, 2017)
This book contains recent advances about CD and NCGS written in eight chapters and is divided in three sections. In the first section, the main hallmarks of both diseases are described, together with the current diagnostic criteria of CD and its influence on the response to the vaccination against hepatitis B virus infection. The second section is dedicated to the description of several techniques for gluten determination in foods and if its consumption is good for nonceliac people. Finally, the third section contains complementary information related to the description and application of novel endoscopic techniques for confirming the diagnosis of CD. Another topic describes the growing consumption of gluten-free products and the adherence to this type of diet.